Polygamy and the Principle of Women’s Protection in the Qur’an: A Thematic Tafsir Study - Muhammadong Muhammadong (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
Polygamy is one of the concerns of Islamic family law that still stimulates discussion, especially on the notion of women’s protection from the standpoint of the Qur’an. The fundamental problem of this study analyzes how the Qur’an perceives polygamy and the application of the values of justice, respect and protection for women in its regulation. The aim of this study is to investigate the notion of polygamy through a thematic interpretation of the Quranic verses connected to polygamy and women’s rights. This research uses a qualitative library research method. The fundamental sources are the verses of the Qur'an concerning polygamy, including Surah An-Nisa verses 3 and 129. The secondary sources are the classical and modern tafsir volumes, books of Islamic law and relevant academic works. The data analysis was carried out utilizing the tafsir maudhu’i approach (thematic interpretation) to analyze the context, meaning, and purposes of the verses. The results reveal that the Qur’an does not give full approval for polygamy, but gives rigorous constraints based on justice, responsibility and fulfillment of women’s rights. A basic aspect for preventing injustice and prejudice is the notion of protecting women. The study indicates that polygamy, from the perspective of the Qur'an, is a restricted permission that should be performed within the bounds of justice, human dignity and societal good.